Uji Intensitas Warna Kuning pada Campuran Sari Kunyit-Daun Salam dan Temulawak Daun Salam Sebangai Pewarna Pangan - Putri Intan Sari; Anny Sartika Daulay; Ridwanto Ridwanto; Haris Munandar Nasution (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Some food industries still use synthetic dyes. Synthetic dyes, if consumed, can harm your health. Turmeric can be used as a natural food coloring. This natural coloring is applied to sweet jelly. This natural coloring agent must be used in fresh juice. To extend the use time of the natural dyes turmeric-bay leaves, ginger-bay leaves, this research was carried out in a variety of storage conditions without using preservatives. The aim of the research was to determine the results of the content of secondary metabolite compounds in turmeric-laurel extract, curcuma-laurel extract, turmeric extract and curcuma extract, in making solid preparations using preservatives, namely citric acid, maltodextin and sucrose. This research uses experimental methods with Sari method is done on a mixture of turmeric-bay leaves and ginger-bay leaves using a water solvent using the distillation method. Determination of variations in storage conditions was carried out for 7 days and the effect of storage temperature. Color stability and intensity measurements were carried out using visible spectrophotometry and characterization methods. The results of this research were obtained. The absorbance intensity test on turmeric-bay leaves was carried out at a wavelength of 425.14 nm with a result of 0.442 (day 1), ginger-bay leaves had an absorbance of 0.490 ( day 1). In the color stability test, there was a change in color from day 3 at drying cupboard temperature, at refrigerator temperature and at room temperature, the color remained stable.